ADAPTING MITCH ALBOM’S TUESDAYS WITH MORRIE TO FILM: CONVEYING LIFE VALUES - Syaifullah; Perrodin, David D (CrossOver Journal of Adaptation Studies, 2023)
Using an adaptation and content analysis approach, this study examined the transformation of Mitch Albom’s novel "Tuesdays with Morrie" into a film. The primary concern was how this adaptation effectively conveyed the message of life values. The adaptation approach was employed to explore disparities in narrative, characters, and themes when a novel is adapted into a film. The content analysis approach was utilized to identify and analyze the portrayal of life values in both mediums. The data collection involved a comprehensive examination of the novel and a screening of the film adaptation. Relevant elements, including dialogues, narratives, characters, and themes pertaining to life values, were identified and documented. Subsequently, content analysis was conducted to identify patterns, themes, and messages concerning life values. The findings revealed that the film adaptation reflected the life values in the novel similarly, despite alterations and simplifications in the story and characters.